Kazi Farms Kitchen (KFK) project of Interspeed Advertisement Ltd. - Masrur, Arshad Ahmed (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2015.